The development of polymeric pellicles with gentamicine sulfate for therapeutic correction of cervical erosion (pseudoerosion) - T. M. Litvinenko (Zaporozhye State Medical University, 2014)
Introduction.Cervical erosionsoccur in 12-15%gynaecological diseases. Erosion is a damage of epithelialmucous membrane or skin. Therapy of patients with cervical erosionsis based on selection of pathogeneticsubstantiative method of treatment. Bathes and irrigations with 20% protargol, alum, carbolic acid, potassium permanganate are used. But some authors admit the destructive influence of these procedures. Using of tampons with 10% sintomycine emulsion, cod liver oil, sea-buckthorn oil,kalanchoe sap, propolis, vagotil, cigerol, galantamine also doesn't give desirable result. Recently polymeric pellicleswith antibacterial substances are widely used. The most perspective in this route are aminoglycoside antibiotics. That is why we chose gentamicine sulfate (broad-spectrum aminoglycoside antibiotic). The aim of study is the development of the optimal composition of vaginal pellicleswith gentamicine sulfate for gynaecological practice, scientifically substantiation of excipients: polymeric base and plasticizer. Results and discussion.Polymeric bases and plasticizers influence on gentamicine sulfate releasing from polimericpellicleshas been studied. Research on choice of optimal composition has been carried out by two-factor experiment plan. The next bases and plasticizers have been used: methylcellulose, sodium carboxymethylcellulose, soluble biopolymer, gelatin; glycerine, propylenglycol, polyethylene glycol, twin 80. Gentamicine sulfate content was 80 mg in one pellicle. Gentamicine sulfate releasing from polimericpellicleshas been investigated by the Kruvchinsky method, concentration of active substance has been detected after 45 min. As a result it has been established that base makes essential influence on the gentamicine sulfate releasing (Fexp.52,88>Ftabl. 3,9). The best plasticizer is glycerin and the most optimal base is gelatin. So the optimal composition for vaginal films has been chosen: Gentamicine sulfate0,08 g Glycerin0,7 g Gelatin0,5 g Water 4 ml Conclusion. Scientificallygrounded choice of pharmaceutical factors (base and plasticizer) has been carried out using mathematic planning for creating gentamicine sulfatepolimericpellicles. Influence of these factors on gentamicine sulfate releasing intensity has been studied.Gelatin base with glycerin provides maximum releasing of active substance.